Perancangan Web untuk Meningkatkan Pemasaran UMKM pada CV Tiga Menara Sejahtera di Masa Pandemi Covid-19 - V.H Valentino (Journal of Academia Perspectives, 2022)
In the current era of the Covid-19 pandemic, it greatly affects the economy of people in the world, especially for the lower middle class, therefore in promoting the results of MSMEs adapting web-based digital technology, so that businesses can continue to run and there are business movements that have been fostered so far, this web design will increase the market share of MSMEs, expand to various groups and distant locations which will later be regulated by the previously discussed agreement which changes the habits that have been carried out so far, therefore all the information listed on the web page on promotions must be in accordance with the real situation of the form offered, so as to make buyers confident when making transactions with this developed business then self-development is given for MSMEs to learn what an e-commerce web is and how to operate web applications such as html, css, html, form layout, page template, javascript etc. Due to the advancement of current web-based technology, MSMEs need to upgrade their knowledge in conducting promotions. Web Hosting is a way of activating a web that is made to be spread over the internet world, through electronic media that is quite close to the community during the pandemic so that all businesses owned can develop rapidly.